2021
DOI: 10.1080/02626667.2021.1918696
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of erosivity density in northwest Italy since 1701

Abstract: Societies can be better prepared to face hydrological extremes (e.g. flash floods) by understanding the trends and variability of rainfall aggressiveness and its derivative, erosivity density (ED). Estimating extended time series of ED is, however, scientifically challenging because of the paucity of long-term high-resolution pluviometric observations. This research presents the longest ED time series reconstruction (1701-2019) in northwest Italy (Piedmont region) to date, which is analysed to identify damagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
1
5
0
Order By: Relevance
“…The two values correspond, respectively, to the median and the 3 rd quartile of the distribution of the RED data (Fig 4A). These values also mark the range of critical RED values identified by Diodato et al [8] with a 50-year return period in north-western Italy. The advantage of using RED threshold values compared to other rainfall aggressiveness indicators are [54]: a) greater propensity to classify geomorphological hazards; b) greater stability, obtained with a shorter and heterogeneous period of recording; and c) easier mapping over large areas due to its independence on altitude up to 3000 m a.s.l.…”
Section: Plos Onesupporting
confidence: 76%
See 2 more Smart Citations
“…The two values correspond, respectively, to the median and the 3 rd quartile of the distribution of the RED data (Fig 4A). These values also mark the range of critical RED values identified by Diodato et al [8] with a 50-year return period in north-western Italy. The advantage of using RED threshold values compared to other rainfall aggressiveness indicators are [54]: a) greater propensity to classify geomorphological hazards; b) greater stability, obtained with a shorter and heterogeneous period of recording; and c) easier mapping over large areas due to its independence on altitude up to 3000 m a.s.l.…”
Section: Plos Onesupporting
confidence: 76%
“…Rainfall erosivity density (RED in MJ hm -2 h -1 , equivalent to the most common MJ ha -1 h -1 ), i.e. rainfall erosivity per unit of rainfall, is an important climatic indicator of floods and soil erosion [ 7 , 8 ]. RED effects are apparent in catastrophic weather events, due to the intensification of daily storms in the northern Hemisphere ( Fig 1A ) and erosive precipitation in other parts of the world ( Fig 1B ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provided, for the first time, drought spatial distribution maps for the whole of northern Italy. The trend analysis indicated that the entire Alpine Range, characterised by the rainiest and snowiest areas (Diodato et al 2021 andTerzago et al 2012), will also experience an increase in drought severity in the RCP 4.5 scenario.…”
Section: Drought Trends and Spatial Behaviourmentioning
confidence: 99%
“…This study provided, for rst time, drought spatial distribution maps for the whole of northern Italy. The trend analysis indicated that the entire Alpine Range, characterised by the rainiest and snowiest areas (Diodato et al 2021 andTerzago et al 2012), will also experience an increase in drought severity in the RCP 4.5 scenario.…”
Section: Drought Trends Spatial Behaviourmentioning
confidence: 99%